The effect of epigallocatechin gallate on Streptococcus Gordonii biofilm formation - Wicaksono, Dimas Prasetianto; Dewi, Ardianti Maartrina; Siti, Ajeng Larisa Asmono; Nuraini, Prawati; Han, Sili (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2024)
Background: Dental caries, as a primary disease in dentistry, is strongly influenced by the presence of biofilms. One of the Gram-positive bacteria that acts as an initiator in the biofilm formation process is Streptococcus gordonii. As the primary catechin in green tea, epigallocatechin gallate (EGCG) is easily found in our daily lives, and it has a broad spectrum of antimicrobial effects. Several studies have revealed that EGCG inhibited the growth of Gram-positive bacteria, including inhibiting biofilm formation by damaging the bacterial cell wall and reducing glucosyltransferase activity. However, there is still limited information that explains the effect of EGCG on S. gordonii bacterial biofilms. Purpose: This study aims to analyze the effect of EGCG in inhibiting the formation of S. gordonii bacterial biofilms. Methods: This study was an in-vitro experimental laboratory study, with samples divided into five groups, namely, the group containing BHIB-bacteria, the BHIB-bacteria-5% sucrose groups, and the treatment groups containing BHIB-bacteria-5% sucrose-EGCG with concentrations of 12.5%, 6.25%, and 3.125%, respectively, incubated for 24 hours. The data was analyzed using the Kruskal–Wallis test. Results: There was a significant difference in the formation of biofilms in S. gordonii bacteria with the addition of 5% sucrose in BHIB compared with the group of S. gordonii bacteria in BHIB. The highest biofilm formation in the group containing bacteria-BHIB-5% sucrose, while the lowest biofilm formation occurred in the treatment group containing bacteria-BHIB-5% sucrose-12.5% EGCG with significant difference between the group. Conclusion: The addition of EGCG 12.5% inhibits the formation of S. gordonii biofilms.